Heat insulation type fireproof composite glass as well as preparation method and application thereof

By introducing multi-layered thermal insulation structures into the fire-resistant glass, including cellulose aerogel core layer and potassium silicate gel layer, the problem of insufficient thermal insulation performance of existing fire-resistant glass is solved, and better thermal insulation and fire-proof effects are achieved.

CN119550700APending Publication Date: 2025-03-04CHINA BUILDING MATERIALS ACADEMY CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411684349.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-22
Publication Date
2025-03-04

AI Technical Summary

Technical Problem

The existing fireproof glass lacks thermal insulation performance in fires, causing rapid heating of the backfire area and causing indoor fires.

Method used

Thermal insulation fire-resistant composite glass is used, which includes a fire-forwarding glass layer, a heat-insulating layer and a backfire glass layer. The thermal insulation layer consists of a cellulose aerogel core layer, a first and second potassium silicate gel layer, and a butyl gel layer. The thermal insulation and fire resistance of the glass are improved through these layers of structures.

Benefits of technology

It significantly improves the thermal insulation and fire resistance of glass, reduces the thermal conductivity of glass, slows down the heating rate of the backfire area, and thus enhances the fire prevention and control capabilities.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119550700A_ABST
    Figure CN119550700A_ABST
Patent Text Reader

Abstract

The invention relates to heat insulation type fireproof composite glass as well as a preparation method and application thereof. The glass comprises a counter-fire glass layer which comprises counter-fire glass; the heat insulation layer is arranged on the surface of the counter-fire glass layer; the heat insulation layer comprises a fiber aerogel core layer; a first potassium silicate gel layer and a second potassium silicate gel layer are arranged on the upper surface and the lower surface of the fiber aerogel core layer, and the counter-fire glass is connected with the heat insulation layer through the first potassium silicate gel layer; butyl rubber layers are arranged on the peripheries of the four vertical side faces of the fiber aerogel core layer. The back fire glass is arranged on the surface of the heat insulation layer, and the back fire glass layer comprises back fire glass; the back fire glass is connected with the heat insulation layer through a second potassium silicate gel layer; the surface of the butyl rubber layer is respectively connected with the counter-fire glass layer and the back-fire glass layer. The technical problem to be solved is how to prepare the glass which has good heat insulation and fireproof performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of glass, and in particular relates to a heat-insulating fire-proof composite glass and a preparation method and application thereof. Background Art

[0002] In today's society, with the development of the construction industry, urban buildings are densely populated. When a fire occurs, in order to protect people's health and resources and property, and to control the spread of fire and smoke when a fire occurs, fireproof glass came into being. Fireproof glass has become one of the important means of national fire prevention. For this reason, the state has also promulgated the national standard GB15763.1-2009 "Safety Glass for Buildings Part 1 Fireproof Glass" to regulate the types of fireproof glass and fire resistance performance evaluation.

[0003] However, with the in-depth study of fire-resistant glass, it was found that although some fire-resistant glass meets national standards, the thermal insulation performance of the glass is poor. After a fire, even if the glass can maintain a certain integrity, its high thermal conductivity will cause the back-fire area to quickly reach a high temperature and ignite indoor items. Therefore, there is still a safety hazard.

[0004] The fireproof laminated glass disclosed in the prior art has a heat insulation and fireproof time of about 1 hour. Although the safety is improved to a certain extent, further improving the heat insulation and fireproof effect of glass is still a major challenge faced by this field. Summary of the invention

[0005] The main purpose of the present invention is to provide a heat-insulating fireproof composite glass and a preparation method and application thereof. The technical problem to be solved is how to provide a glass with good heat-insulating and fireproof properties.

[0006] The purpose of the present invention and the technical problem to be solved are achieved by adopting the following technical solutions. According to the present invention, a heat-insulating fire-resistant composite glass is proposed, which comprises:

[0007] The fire-facing glass layer comprises fire-facing glass;

[0008] A heat-insulating layer is arranged on the surface of the fire-facing glass layer; the heat-insulating layer comprises a fiber aerogel core layer; a first potassium silicate gel layer and a second potassium silicate gel layer are arranged on the upper and lower surfaces of the fiber aerogel core layer, and the fire-facing glass is connected to the heat-insulating layer through the first potassium silicate gel layer; a butyl rubber layer is arranged on the periphery of four vertical side surfaces of the fiber aerogel core layer;

[0009] The back-fire glass is arranged on the surface of the thermal insulation layer, the back-fire glass layer includes the back-fire glass; the back-fire glass and the thermal insulation layer are connected through a second potassium silicate gel layer; the surface of the butyl rubber layer is respectively connected to the front-fire glass layer and the back-fire glass layer.

[0010] The purpose of the present invention and the solution to its technical problems can be further achieved by adopting the following technical measures.

[0011] Preferably, in the aforementioned glass, the front-fire glass and the back-fire glass are both borosilicate glass.

[0012] Preferably, in the aforementioned glass, the potassium silicate gel layer contains 15-30% by mass of SiO2; and the thickness of the first potassium silicate gel layer is 1-5 mm.

[0013] Preferably, in the aforementioned glass, the cellulose aerogel layer has a porosity of 95.0-99.5% and a pore size of ≤20 nm.

[0014] Preferably, in the aforementioned glass, the cellulose aerogel layer has a thickness of 6 to 10 mm.

[0015] Preferably, in the aforementioned glass, a single side of the fire-facing glass away from the heat insulation layer is coated with an ITO conductive film and a SiO2 protective layer from the inside to the outside.

[0016] The purpose of the present invention and the technical problem solved by the present invention are also achieved by adopting the following technical solutions. According to the present invention, a method for preparing heat-insulating fire-resistant composite glass is proposed, which comprises the following steps:

[0017] S71: cellulose aerogel is bonded to the middle position of the back-fired glass through potassium silicate gel;

[0018] S72 A butyl rubber layer is adhered to the back-fired glass around the outer side of the cellulose aerogel;

[0019] S73: bonding a fire-facing glass to the butyl rubber layer; the fire-facing glass, the butyl rubber layer, and the cellulose aerogel form a cavity;

[0020] S74: Fill the cavity with potassium silicate gel.

[0021] The purpose of the present invention and the solution to its technical problems can be further achieved by adopting the following technical measures.

[0022] Preferably, in the aforementioned method, the preparation of the cellulose aerogel comprises the following steps:

[0023] Take a TEMPO aqueous solution with a mass concentration of 10-15% and a fiber suspension with a fiber mass percentage of 0.5-1%;

[0024] Adding the TEMPO aqueous solution dropwise into the fiber suspension to form an oxidized fiber suspension, wherein the pH of the fiber suspension system is 9 to 10 during the addition process, and the volume percentage of the TEMPO aqueous solution in the oxidized fiber suspension is 20 to 30%;

[0025] The oxidized fiber suspension is centrifuged to remove impurities, thereby obtaining a target fiber suspension; the fiber mass percentage in the target fiber suspension is 0.3-0.5%;

[0026] The target fiber suspension is freeze-formed and freeze-dried in sequence to obtain cellulose aerogel.

[0027] Preferably, in the aforementioned method, the wood pulp fibers of the fiber suspension are derived from hardwood.

[0028] Preferably, in the aforementioned method, the preparation of the potassium silicate sol comprises the following steps:

[0029] The SiO2 nanoparticle dispersion and the boron-containing potassium hydroxide solution are stirred and mixed at a temperature of 50 to 60° C. to form the potassium silicate sol;

[0030] The SiO2 nanoparticle dispersion contains an anionic surfactant;

[0031] The mass percentage of SiO2 in the potassium silicate sol is 15-30%.

[0032] Preferably, in the aforementioned method, before the fire-facing glass is tempered, the side of the fire-facing glass away from the thermal insulation layer is coated with an ITO transparent conductive film and a SiO2 protective layer from the inside to the outside.

[0033] The purpose of the present invention and the technical problems solved therein are also achieved by adopting the following technical solutions: The heat-insulating fire-resistant composite glass proposed according to the above-mentioned solution of the present invention can be applied to the fields of construction, transportation, and industrial equipment.

[0034] By means of the above technical solution, the heat-insulating fire-resistant composite glass and its preparation method and application proposed by the present invention have at least the following advantages:

[0035] 1. The present invention provides a heat-insulating fireproof composite glass, which has a fire-facing glass layer, a heat-insulating layer, and a back-fire glass layer arranged in sequence; the cellulose aerogel and potassium silicate gel layer arranged in the heat-insulating layer and the special structure of the two make the glass have good heat-insulating and fire-proof performance; and a butyl rubber layer is arranged around the cavity formed by the fire-facing glass and the back-fire glass layer to block external water vapor from entering the heat-insulating layer, so as to maintain the good fireproof and heat-insulating performance of the composite glass. In addition, the special structure of the potassium silicate gel layer helps to reduce or even eliminate the optical reflection of the interface formed by the fiber aerogel layer, glass, and air, reduce the haze of the glass, and improve the overall visible light transmittance.

[0036] 2. The present invention also provides a method for preparing heat-insulating fireproof composite glass. This method not only realizes the sequential connection of the fire-facing glass layer, the heat-insulating layer, and the back-fire glass layer, but also forms a cavity between the fire-facing glass and the butyl rubber layer and the cellulose aerogel to prepare a potassium silicate gel layer with a certain thickness, so that the prepared composite glass has good appearance, high light transmittance, and good heat-insulating and fireproof effects.

[0037] The above description is only an overview of the technical solution of the present invention. In order to more clearly understand the technical means of the present invention and implement it according to the contents of the specification, the following is a detailed description of the preferred embodiments of the present invention in conjunction with the accompanying drawings. BRIEF DESCRIPTION OF THE DRAWINGS

[0038] Figure 1 This is a schematic diagram of the structure of the heat-insulating fire-resistant composite glass of the embodiment;

[0039] Figure 2 This is the transmittance change diagram of coated borosilicate glass before and after enhancement;

[0040] Figure 3 Internal temperature rise curves of fire resistance test of Example 1 and Comparative Example 1. DETAILED DESCRIPTION

[0041] In order to further explain the technical means and effects adopted by the present invention to achieve the predetermined invention purpose, the following is a heat-insulating fire-resistant composite glass and its preparation method and application proposed by the present invention in combination with the accompanying drawings and preferred embodiments. Its specific implementation method, structure, characteristics and effects are described in detail as follows.

[0042] The thickness described below, such as the potassium silicate gel layer, cellulose aerogel layer, ITO film, SiO2 protective layer, and structure thickness, refers to the dimension of each structural layer in the direction perpendicular to the facing fire glass layer and the back fire glass layer.

[0043] like Figure 1 As shown, the present invention provides a heat-insulating fire-proof composite glass (hereinafter referred to as "composite glass"), which includes a fire-facing glass layer, a heat-insulating layer and a back-fire glass layer which are sequentially connected and arranged.

[0044] In some embodiments, the fire-facing glass layer includes the fire-facing glass 10; the back-fire glass layer includes the back-fire glass 20; the thickness of the fire-facing glass and the back-fire glass can be of any specification; in some embodiments, the thickness of the glass is 5mm, 6mm, or 8mm; preferably, in order to increase the heat-insulating and fire-proofing effect of the composite glass, in some embodiments, both the fire-facing glass layer and the back-fire glass layer are made of borosilicate glass to extend the overall fire resistance time of the composite glass.

[0045] In some embodiments, the thermal insulation layer includes a fiber aerogel layer 30; the fiber aerogel layer is used to increase the thermal insulation effect of the composite glass, and the cellulose aerogel used in the present invention can be derived from wood pulp, has low cost, and the porous structure of the formed aerogel has high porosity, and the composite glass formed by the cellulose aerogel and the glass body has good light transmittance.

[0046] Furthermore, in some embodiments, preferably, the thermal insulation layer is also provided with a first potassium silicate gel layer 40 connected to the fire-facing glass layer, and a second potassium silicate gel layer 41 connected to the heat insulation layer and the back-fire glass layer, so that the heating rate of the glass body is significantly reduced, and the glass has a certain flame retardant effect; further, since the cellulose aerogel has a large specific surface area, the potassium silicate gel can be firmly and fully adsorbed on the surface of the cellulose aerogel to eliminate the interface optical reflection formed by the fiber aerogel layer, glass, and air, reduce the glass haze, and improve the overall visible light transmittance of the composite glass; at the same time, the cellulose aerogel has a large specific surface area and good adsorption effect, which can inhibit the decomposition and aging of the potassium silicate gel and extend the service life of the composite glass.

[0047] Furthermore, in some embodiments, the four sides of the cellulose aerogel layer are provided with a butyl rubber layer 50 connected to both the fire-facing glass layer and the back-facing glass layer, that is, the butyl rubber layer is clamped by the fire-facing glass and the back-facing glass. This helps to isolate external water vapor from entering the insulation layer, especially from entering the cellulose aerogel layer, and avoids changes in the structure of the composite glass insulation layer, thereby helping to maintain the thermal insulation and fireproofing effects of the glass, and also helping to extend the service life of the composite glass.

[0048] In other embodiments, the thermal insulation layer comprises a cellulose aerogel core layer, and potassium silicate gel is used to fully cover the cellulose aerogel core layer to form a core-shell structure, that is, the core layer is cellulose aerogel and the shell layer is potassium silicate gel; this helps to improve the overall thermal insulation and flame retardant properties of the composite glass. Further, in other embodiments, butyl rubber layers are arranged on the four sides of the potassium silicate gel as the shell layer, and the upper and lower surfaces of the butyl rubber layer are respectively connected to the fire-facing glass and the back-fire glass to isolate external water vapor from entering the thermal insulation layer.

[0049] The thicker the potassium silicate gel layer, the more conducive it is to eliminating the optical reflection effect of the interface formed by the fiber aerogel layer, glass, and air in the composite glass, and it is beneficial to improve the thermal insulation and fireproof performance of the glass body, but this may reduce the light transmittance of the composite glass; similarly, the higher the content of SiO2 added to the potassium silicate gel layer, the more conducive it is to eliminating the optical reflection effect of the interface formed by the fiber aerogel layer, glass, and air. However, when the SiO2 content is too high, it may be detrimental to the transmission of light, and thus may reduce the light transmittance of the composite glass. In order to balance the light transmission effect of the composite glass of the present invention, some embodiments preferably have a potassium silicate gel layer with a thickness of 1 to 5 mm between the fire-facing glass layer and the fiber aerogel layer, and the potassium silicate gel layer contains 15 to 30% SiO2 by mass.

[0050] The higher the porosity of the cellulose aerogel and the larger the pore size, the more helpful it is to improve the light transmittance of the composite glass. However, as the pore size increases, the light scattering effect of the light in the cellulose aerogel layer is correspondingly enhanced, which may reduce the light transmittance of the composite glass. Preferably, in some embodiments of the present invention, the porosity of the fiber aerogel layer is 95.0-99.5%, and the pore size is ≤20nm; further preferably, the porosity of the fiber aerogel layer is 98.0-99.5%, and the pore size is ≤15nm; further preferably, the pore size is evenly distributed in the cellulose aerogel, and the difference between the pore sizes is small, the pore size of the fiber aerogel layer is 10-15nm, and the prepared composite glass has good light transmittance.

[0051] When the thickness of the cellulose aerogel layer increases, it helps to enhance the thermal insulation effect of the composite glass, but the corresponding light transmittance may decrease; accordingly, when the thickness of the cellulose aerogel layer decreases, the thermal insulation of the composite glass may decrease. In order to better balance the light transmittance and thermal insulation effect of the composite glass, the present invention preferably has a cellulose aerogel layer thickness of 6 to 10 mm.

[0052] The above technical solution, in some embodiments, Figure 1As shown, an ITO transparent conductive film (hereinafter referred to as "ITO film") 11 and a SiO2 protective layer 12 are coated on the surface of the fire-facing glass layer from the inside to the outside. The ITO film is used to reflect infrared heat radiation, which helps to suppress the heating rate of the composite glass, and the heat insulation effect of the composite glass is also improved. SiO2 as the outermost layer can protect the ITO film from being scratched by subsequent processes; more importantly, since the SiO2 protective layer has a low light refractive index and the ITO film has a high light refractive index, coating the SiO2 protective layer on the outside of the ITO film helps to reduce the light lost due to refraction before entering the fire-facing glass, thereby increasing the transmittance of the ITO film coated on the glass by more than 5%. Since the SiO2 protective layer is too thick, it is not conducive to the incidence of light into the fire-facing glass. Preferably, in some embodiments, the thickness of the SiO2 protective layer is 60 to 90 mm; further preferably, the thickness of the SiO2 protective layer is 70 to 90 mm.

[0053] The above technical solution, in some embodiments, is further preferably Figure 1 As shown, a silicone adhesive layer 60 is arranged outside the butyl adhesive layer to increase the bonding tightness and firmness of the overall structure of the composite glass body. In some embodiments, it is further preferred that the butyl adhesive layer and the silicone adhesive layer have the same dimensions in a direction parallel to both the fire-facing glass layer and the back-fire glass layer, which can not only effectively prevent external water vapor from entering the heat insulation layer, but also ensure the bonding tightness and firmness of the overall structure of the composite glass.

[0054] Some embodiments of the present invention also provide a method for preparing a heat-insulating fire-resistant composite glass, which is as follows:

[0055] 1) The cellulose aerogel is bonded to the middle position of the back-fired glass via potassium silicate gel; in some embodiments, the back-fired glass is pressed onto a single side of the cellulose aerogel layer coated with potassium silicate sol, and the cellulose aerogel is adsorbed on the glass with the help of the bonding effect of the potassium silicate sol. In order to facilitate the subsequent use of butyl tape to firmly bond the glass layer and the aerogel layer, preferably, there are blank glass areas not covered by cellulose aerogel around the sides where the back-fired glass and the cellulose aerogel are bonded, that is, the cellulose aerogel layer cannot completely cover a single side of the back-fired glass, and the length and width of the cellulose aerogel layer are smaller than the corresponding length and width values ​​of the back-fired glass; further preferably, the cellulose aerogel layer is located in the center of the plane of the back-fired glass.

[0056] The cellulose aerogel can be purchased or prepared by oneself.

[0057] Preferably, in some embodiments of the present invention, the cellulose aerogel is prepared by the following method:

[0058] Preparing wood pulp fibers: The present invention preferably uses light and soft broad-leaved wood pulp fibers as raw materials; further preferably, in some embodiments, eucalyptus wood pulp fibers are used as raw materials; further preferably, in other embodiments, poplar wood pulp fibers are used as raw materials; the present invention optimizes the raw wood pulp for preparing cellulose aerogel so that the prepared cellulose aerogel has a small density and a light texture, and the prepared cellulose aerogel is easier to adsorb potassium silicate sol, and the prepared composite glass has a higher light transmittance, a small glass density, and a wide range of applications.

[0059] Take wood pulp fibers with a fiber mass percentage of 0.5-1% (can be prepared by yourself or purchased from the market), add deionized water to the wood pulp fibers, and continue stirring at a speed of 1000-1200 rpm for 10-12 hours. Break up the fibers through mechanical stirring to mix them evenly to form a fiber suspension, and let it stand at room temperature to remove bubbles.

[0060] Preparation of oxidant solution: Deionized water is used to prepare an oxygen-enhancing agent sodium hypochlorite (NaClO) solution, the mass concentration of the sodium chlorate (NaClO) solution is 5-10%, and then an oxidant 2,2,6,6-tetramethyl-1-piperidinyloxy free radical (TEMPO) is added to obtain a TEMPO oxidant solution with a mass concentration of 10-15%.

[0061] Cellulose oxidation: In some embodiments, the oxidant solution is added dropwise to the fiber suspension at a dropping speed of 5 to 8 mL / min. The cellulose suspension is stirred at 800 to 1000 rpm during the dropping process. The pH of the cellulose suspension system is maintained in the range of 9 to 10. When the pH is greater than 10, the dropping should be stopped. When the pH is less than 9, the dropping speed can be increased. After each continuous dropping for 10 minutes, the dropping should be stopped and stirring should be continued for 30 to 40 minutes; an oxidized fiber suspension is obtained; in the oxidized fiber suspension, the total volume of the oxidant solution added accounts for 20 to 30%.

[0062] The oxidized fiber suspension is subjected to high-speed centrifugation to remove impurities (centrifugal speed ≥ 1500rpm), the upper centrifuge liquid is removed, the lower centrifuge liquid is collected, and deionized water is added to continue centrifugation to remove impurities. When the suspension is completely separated into upper and lower layers, the upper clear liquid is removed and the lower centrifuge liquid is collected, which is the target fiber suspension. The fiber mass percentage in the target fiber suspension is 0.3-0.4%.

[0063] The target fiber suspension is quantitatively placed in a mold, and the whole is further placed in liquid nitrogen for freezing treatment so that the dispersion is completely frozen, and then the frozen gel is dried in a freeze dryer at -50 to -65°C and 1 to 5 Pa for 70 to 75 hours to obtain a cellulose aerogel. The vacuum degree during the freeze drying process is <1 Pa. Preferably, the mold is a corrosion-resistant material. In some embodiments, the mold is a polytetrafluoroethylene tank.

[0064] The cellulose aerogel finally prepared by the above scheme has a porosity of 95.0-99.5%, a thermal conductivity of <0.025W / (m·K), and a density of 3-4mg / cm 3 .

[0065] Preferably, in the aforementioned technical solution, the method for preparing the potassium silicate sol is as follows:

[0066] Prepare SiO2 nanoparticle dispersion: take deionized water and adjust the pH value to 10-11 with ammonia water, then add anionic surfactant, the anionic surfactant is preferably a mixture of one or more of fatty alcohol alkyl sulfonate, alkylamine ester, and lauryl alcohol phosphate, and sodium dodecyl sulfate is further preferred. The concentration of the surfactant is required to be 0.8-1.2×10 -3 mol / L; heat the surfactant-containing solution to 50-60°C. Further, SiO2 nanoparticles with a purity of ≥95% (i.e., the mass percentage of SiO2 in the SiO2 nanoparticles) are selected, and more preferably, the purity of the SiO2 nanoparticles is ≥98%, and more preferably, the purity of the SiO2 nanoparticles is ≥99%, and more preferably, the particle size of the SiO2 nanoparticles is 10-50nm; the present invention optimizes the purity and particle size of the SiO2 nanoparticles, which helps to improve the uniformity and stability of the prepared potassium silicate sol, and further helps to improve the light transmittance of the prepared glass; SiO2 nanoparticles are added to the surfactant-containing solution at a speed of 8-10g / min, and the solution is always in a stirring state (800-1000rpm rotation speed). The SiO2 solid content in the finally formed SiO2 nanoparticle dispersion is 30-40%.

[0067] In this step, only anionic surfactant is used, and its concentration is 0.8-1.2×10 -3 mol / L, which not only makes the SiO2 nanoparticle dispersion maintain solution stability, dispersion viscosity stable, but also reduces foaming; further preferably, the SiO2 nanoparticle dispersion has a SiO2 solid content of 30-40%, which can make the refractive index of the gel formed by the sol close to that of borosilicate glass and cellulose aerogel, and help to improve the light transmittance of the glass.

[0068] The boron-containing potassium hydroxide solution is prepared by dissolving potassium hydroxide in deionized water to form a potassium hydroxide solution with a mass percentage of 15-20%, and then adding a surfactant, wherein the surfactant accounts for 5-10% by volume in the formed potassium hydroxide solution containing an active agent; the potassium hydroxide solution containing a surfactant is heated to 50-60° C.; then borax (Na2B4O7·10H2O) is added at a speed of 2-5 g / min, and the solution is always in a stirring state (800-1000 rpm rotation speed), and the mass percentage of boric acid in the boron-containing potassium hydroxide solution borax is finally prepared to be 2-4%. The surfactant of the present invention is preferably a mixture of one or more of glycerol, ethylene glycol, and sorbitol; glycerol is further preferred, because the material is cheap and the effect is good.

[0069] Mix the SiO2 nanoparticle dispersion at 50-60°C and the boron-containing potassium hydroxide solution, in which the volume of the SiO2 nanoparticle dispersion accounts for 60-70%, and mix and stir at 800-1000 rpm for 15-20 minutes to form a potassium silicate sol, which can directly enter the next process step; or the solution is naturally cooled to room temperature, and then the solution is always in a closed and stirred state, and stored waiting to enter the next process step, and the storage period can reach 5-7 days. The prepared potassium silicate sol has a wetting angle of less than 10° on the surface of glass and aerogel, and the refractive index of the gel formed is 1.2-1.3, which can play a flame retardant role.

[0070] 2) A butyl rubber layer is attached to the back-fired glass around the outer side of the cellulose aerogel; a butyl rubber layer is laid in the blank glass area of ​​the bonding surface between the back-fired glass and the cellulose aerogel layer, that is, the position not covered by the cellulose aerogel layer, to form a Figure 1 A butyl rubber area 50 is shown.

[0071] 3) Bonding the fire-facing glass to the butyl rubber layer; the fire-facing glass, the butyl rubber layer and the cellulose aerogel form a cavity; in some embodiments, the height of the rubber strip perpendicular to the glass is h1, and the height of the cellulose aerogel perpendicular to the glass is h2. Preferably, h1>h2 so that a cavity can be formed between the cellulose aerogel layer and the fire-facing glass and the butyl rubber layer, so that a thicker potassium silicate gel layer can be formed later to meet the design requirements of the present invention; in some embodiments, h1 is 11-20 mm, which is 1-5 mm higher than the height h2 of the cellulose aerogel layer. In other embodiments, h1 is 11-16 mm, which is 1-2 mm higher than the height h2 of the cellulose aerogel layer. Press the fire-facing glass onto the butyl rubber strip to form a composite layer. Heat the formed composite layer to 100-120°C, and press to tightly connect the layers. In some embodiments, a roller press is used to firmly bond the two pieces of glass to the butyl rubber strip.

[0072] 4) Fill the cavity with potassium silicate gel. In some embodiments, holes are punched at the butyl rubber strips in the diagonal areas of the composite layer glass, and inlets and outlets are set to place the composite layer in three dimensions. In some embodiments, the inlet is in the bottom angle area of ​​the composite layer glass, and the outlet is in the top angle area of ​​the composite layer glass; potassium silicate sol is injected from the inlet, and after the composite layer is filled with potassium silicate sol and all bubbles inside the composite layer are removed from the outlet, the inlet and outlet are blocked in sequence with butyl rubber. Preferably, in some embodiments, the diameter of the inlet and outlet formed is 0.5 to 1 mm, which can not only quickly inject the sol, but also help to ensure that the bubbles inside the composite layer can be exhausted, and the butyl rubber strip seals the inlet and outlet to prevent liquid from seeping out or external gas from entering. Preferably, in the aforementioned technical solution, in some embodiments, silicone glue is also injected along the edge of the composite layer to fill the empty groove space at the edge of the butyl rubber strip and the glass, and then naturally solidifies. Preferably, in the direction parallel to the fire-facing glass layer and the back-facing glass layer, the scale of the butyl rubber layer is consistent with that of the silicone rubber layer, so that the overall structural stability of the prepared composite glass is good and external water vapor is effectively blocked from entering the insulation layer.

[0073] In some embodiments, before the back-fired glass and the cellulose aerogel layer are bonded, the glass used for the front-fired glass layer and the back-fired glass layer is subjected to a tempering pretreatment; the tempering pretreatment is performed by a conventional method.

[0074] Further preferably, in some other embodiments, the surface of the fire-facing glass is coated with an ITO film and a SiO2 protective layer from the inside to the outside before being tempered, so as to enhance the heat insulation effect of the prepared composite glass and improve the light transmittance of the glass. The specific method is as follows:

[0075] Before glass coating, it is cleaned by deionized water roller brush, disk brush, ultrasonic cleaning, air drying and hot air drying.

[0076] ITO film coating: Use flat ITO ceramic target and magnetron sputtering process to coat the film. The power density required in this application is 0.3-0.5W / mm 2 Within the range, the O2 flow rate shall not exceed 2% of the total flow rate of Ar and O2, the working pressure is 0.2-0.4Pa, and the ITO film thickness is 300-400nm. If it exceeds the process parameter setting range and the film thickness range of the present invention, the film transmittance and surface resistance performance may not be improved in the subsequent tempering and strengthening process, and defects such as film shedding and spots will be aggravated. Increasing the film thickness can reduce the surface resistance. The lower the resistance, the better the reflection of thermal radiation, but the transmittance will be reduced. It can be designed according to different architectural appearance requirements. The thickness can be adjusted by the speed and power of the glass under the target.

[0077] SiO2 protective layer: using rotating Si target, magnetron sputtering process coating. In some embodiments, the process parameters are as follows: power density 0.1-0.2W / mm 2 The ratio of O2 flow rate to the total flow rate of Ar and O2 shall not be greater than 10%, the working gas pressure is 0.2-0.4Pa, and the SiO2 film thickness is 60-90nm. If the process parameter setting range and the film thickness of the present invention are exceeded, the transmittance and surface resistance performance of the film may not be improved during the subsequent tempering and strengthening process. A film thickness lower than 60nm may result in a decrease in transmittance, and a film thickness exceeding 90nm may result in an increase in surface resistance and a decrease in the ability to block infrared radiation.

[0078] Further preferably, in some embodiments, the fire-facing glass is treated with a coating. In order to ensure that the performance of the film coated on the surface of the fire-facing glass is good, the fire-facing glass is subjected to a heating and then rapid cooling method to form prestress on the glass surface during the tempering process to achieve a tempered and enhanced effect. In addition to successfully tempering and strengthening the glass, this method can more importantly improve the transmittance of the ITO film and reduce the surface resistance through the glass heating process, and the ITO film reduces the heating efficiency.

[0079] Further, in some embodiments, the tempering process of the coated glass is different from the tempering process of ordinary glass, and the tempering process is as follows:

[0080] The radiation and convection heating method is adopted, the heating temperature is 845-860℃, the reciprocating swing speed is 240-270mm / s, the heating time of 5mm glass is 250-260s; the heating time of 6mm glass is 300-360s; the heating time of 8mm glass is 400-480s; the heating temperature needs to be lowered, the heating time needs to be increased, and the swing speed needs to be reduced as the glass thickness increases. The smaller the initial surface resistance of the film, the longer the heating time needs to be, but it needs to be controlled within the above requirements. Low heating temperature and short time may cause the performance of the ITO film to not be fully improved, and too low swing speed will cause the glass deformation to increase. After the coated glass is heated, it is blown to cool rapidly, with a wind pressure of 0.3-0.5MPa. The cooling time is affected by the seasonal environment and is controlled at 40-120s in summer and shortened appropriately in winter.

[0081] Furthermore, in some embodiments, for the fire-facing glass with a film layer coated on one side, during the process of bonding the fire-facing glass to the butyl adhesive layer, the film layer of the fire-facing glass is away from the heat insulation layer.

[0082] By using the heat-insulating and fire-proof composite glass and the preparation method thereof provided by the present invention, the obtained glass material has good fireproof performance, good heat-insulating effect, slow glass heating speed, good light transmittance, low preparation cost, and is easy to produce and use.

[0083] The present invention will be further described below in conjunction with specific embodiments, but this should not be construed as limiting the scope of protection of the present invention. Some non-essential improvements and adjustments made to the present invention by technicians in this field based on the above-mentioned contents of the present invention still fall within the scope of protection of the present invention.

[0084] Unless otherwise specified, the materials, reagents, etc. involved below are all commercially available products well known to those skilled in the art; unless otherwise specified, the methods described are all methods well known in the art. Unless otherwise defined, the technical terms or scientific terms used should have the common meanings understood by ordinary technicians in the field to which the present invention belongs.

[0085] The purity of the SiO2 nanoparticles used in the examples and comparative examples of the present invention is ≥95%, and the particle size is 10-50 nm.

[0086] Example 1

[0087] 1. Glass pretreatment:

[0088] (1) Cut 6 mm borosilicate glass into a size of 1000 mm × 800 mm, grind the edges, and then use deionized water roller brush, disk brush cleaning, ultrasonic cleaning, air drying, and hot air drying.

[0089] On one side of the fire-facing glass, an ITO transparent conductive film and a SiO2 protective layer are plated from the inside to the outside, as follows:

[0090] ITO thin film coating: In a clean environment, the glass is sent into a vacuum chamber to prepare infrared radiation blocking ITO thin film. The sputtering target power density is 0.3W / mm 2 , working gas pressure 0.3Pa, Ar flow rate 100ccm, O2 flow rate 1sccm, coating film thickness is 300nm, the obtained ITO thin film surface resistance is 24Ω / □, and the transmittance is 75%.

[0091] SiO2 protective layer coating: sputtering target power density 0.1W / mm 2 , working gas pressure 0.2Pa, Ar flow rate 100ccm, O2 flow rate 10sccm, and the coating film thickness is 80nm.

[0092] Tempered strengthening of coated fire-facing glass: adopts radiation and convection heating, heating temperature 850℃, reciprocating swing speed 260mm / s, heating time 350s, after heating, the coated glass is blown for rapid cooling, wind pressure 0.4MPa, cooling time 100s. After this strengthening process, the surface resistance of the fire-facing glass can reach 12.4Ω / □, transmittance 89.1%, and the transmittance of the glass before and after strengthening is as follows Figure 2 shown.

[0093] The thickness of the borosilicate glass on the back of the fire is also 6mm. It is processed and cut to a size of 1000mm×800mm. After edge grinding and cleaning, it is tempered and strengthened. The heating temperature is 830℃, the reciprocating swing speed is 245mm / s, the heating time is 240s, and the heating time for 8mm glass is 300s. After heating, it is quickly cooled by blowing with an air pressure of 0.3MPa. The cooling time is controlled within 100s due to the influence of ambient temperature.

[0094] 2. Preparation of cellulose aerogel

[0095] (1) Preparation of cellulose suspension: 100 g of bleached eucalyptus pulp fiber was added with deionized water to form a mixed solution, wherein the fiber solid content in the mixed solution was 0.6% by weight; the mixture was stirred at 1100 rpm for 12 h to break up the fibers by mechanical stirring to form a uniformly mixed fiber suspension, and then allowed to stand at room temperature to remove bubbles.

[0096] (2) Preparation of oxidant solution: Deionized water was used to prepare an oxygen-enhancing agent sodium hypochlorite (NaClO) solution, wherein the mass concentration of the sodium chlorate (NaClO) in the formed solution was 8%, and then an oxidant 2,2,6,6-tetramethyl-1-piperidinyloxy free radical (TEMPO) was added to obtain a TEMPO oxidant solution with a mass concentration of 12%.

[0097] (3) Preparation of oxidized fiber suspension: The oxidant solution is added dropwise to the fiber suspension at a rate of 6 mL / min. During the addition process, the mixed liquid system is stirred at 1000 rpm, and the pH of the mixed liquid system is maintained at 9-10. After each continuous addition for 10 minutes, the addition needs to be stopped and the stirring is continued for 30 minutes to obtain an oxidized fiber suspension, in which the volume proportion of the oxidant solution in the oxidized fiber suspension is 25%. The oxidized fiber suspension is subjected to high-speed centrifugation to remove impurities, and finally a target fiber suspension with a fiber mass percentage of 0.35% is obtained.

[0098] (4) Molding: The stirred target fiber suspension is quantitatively loaded into a polytetrafluoroethylene tank mold, and then the whole is placed in liquid nitrogen for freezing treatment until the dispersion is completely frozen; the frozen gel is further placed in a freeze dryer for drying at -55°C and 3Pa for 72 hours to obtain a cellulose aerogel. The obtained cellulose aerogel has a porosity of 99.28%, a pore size of 10-15nm, a thermal conductivity of 0.022W / (m·K), and a density of 3.9mg / cm 3 .

[0099] 3. Preparation of potassium silicate sol

[0100] (1) Preparation of SiO2 nanoparticle dispersion: Deionized water was taken and the pH value was adjusted to 10-11 with ammonia water, and then anionic surfactant sodium dodecyl sulfate was added. The concentration of the surfactant was 1.0×10-3 mol / L; the surfactant solution is heated to 55°C; SiO2 nanoparticles are added to the surfactant solution at a rate of 8g / min, and the solution is always in a stirring state. The mass percentage of SiO2 in the SiO2 nanoparticle dispersion is 35%.

[0101] (2) Preparation of boron potassium hydroxide solution: Potassium hydroxide is dissolved in deionized water to form a potassium hydroxide solution with a mass concentration of 15%, and then a surfactant, propylene glycol, is added to form a mixed solution, in which the volume proportion of propylene glycol in the mixed solution is 5%; the potassium hydroxide solution containing the surfactant is heated to 60° C.; borax (Na2B4O7·10H2O) is added to the potassium hydroxide solution containing the surfactant at a rate of 2 g / min, and the solution system is always in a stirring state. The mass content of borax in the finally formed solution is 2%.

[0102] (3) Preparation of potassium silicate sol: SiO2 nanoparticle dispersion at a temperature of 50-60°C and boron-containing potassium hydroxide solution are mixed, with the volume of SiO2 nanoparticle dispersion accounting for 62% of the mixed solution. After mixing and stirring for 20 minutes, potassium silicate sol is formed.

[0103] Preparation of heat-insulating fire-resistant glass:

[0104] (1) The cellulose aerogel is cut into 975×775 mm according to the size of glass, and its thickness is 8 mm. Potassium silicate sol is coated on the surface of the cellulose aerogel, and the back-fired glass is evenly pressed on the plane of the cellulose aerogel.

[0105] (2) A composite butyl rubber strip is laid in the blank area around the bonding surface between the back-fired glass and the cellulose, and the butyl rubber layer on the back-fired glass is higher than the cellulose aerogel.

[0106] (3) Press the fire-facing glass onto the composite butyl rubber strip, with the coated surface away from the cellulose aerogel, heat the whole to 110°C, and pass it through a roller press to firmly bond the two pieces of glass to the composite butyl rubber strip to form a composite layer. The fire-facing glass, cellulose aerogel, and butyl rubber layer form a cavity.

[0107] (4) After all the glass is bonded, place it in three dimensions, and punch 0.5mm holes inward at the diagonal positions of the composite butyl strips of the composite layer of glass to form injection holes and exhaust holes; inject potassium silicate sol from the lower side holes, and after the potassium silicate sol is filled and all bubbles inside the composite layer are removed, use butyl glue to inject the glue holes and exhaust holes. Then inject silicone glue along the edge of the glass to fill the empty space between the composite butyl strips and the edge of the glass.

[0108] (5) After the potassium silicate sol is injected, the composite layer is left to stand for 48 hours, and potassium silicate gel is formed inside the composite layer, thereby forming the heat-insulating fire-resistant composite glass of the present invention.

[0109] The thickness of the potassium silicate gel layer between the fire-facing glass layer and the cellulose aerogel in the prepared heat-insulating fire-proof composite glass is 2 mm, and the thickness of the cellulose aerogel layer is 8 mm.

[0110] Observe the appearance of the formed heat-insulating fire-resistant composite glass, test the glass transmittance, haze, and heat-insulating fire-resistant effects. The test method is as follows:

[0111] Glass light transmittance: Haze is in accordance with GB / T 7962.16-2010 colorless optical glass test method;

[0112] Thermal insulation and fire resistance test: Tested in accordance with GB / T 12513-2006 Fire resistance test method for glazed components.

[0113] The test results are shown in Table 1.

[0114] Example 2

[0115] The main difference between this embodiment and embodiment 1 is that:

[0116] 1) During the preparation of cellulose aerogel, the target fiber suspension was 0.3%. By adjusting the process parameters of cellulose aerogel, the pore size of the prepared cellulose aerogel was 10-18 nm and the porosity was 98%.

[0117] 2) During the preparation of potassium silicate sol, the surfactant used in the SiO2 nanoparticle dispersion is alkylamine ester, and the mass percentage of SiO2 in the SiO2 nanoparticle dispersion is 30%; during the preparation of the boron-containing potassium hydroxide solution, the surfactant is ethylene glycol, and the mass content of borax is 3%; the mass percentage of SiO2 in the potassium silicate sol is 15%.

[0118] 3) In the prepared heat-insulating protective glass, the SiO2 protective layer coated on the surface of the fire-facing glass is 60nm, the thickness of the cellulose aerogel is 6mm, and the thickness of the potassium silicate sol between the cellulose aerogel layer and the fire-facing glass is 1mm.

[0119] The appearance of the formed heat-insulating fireproof composite glass was observed, and the light transmittance, haze, and heat-insulating fire-resistant effect of the glass were tested. The testing method was the same as in Example 1. The test results are shown in Table 1.

[0120] Example 3

[0121] The main difference between this embodiment and embodiment 1 is that:

[0122] 1) During the preparation of cellulose aerogel, the target fiber suspension was 0.4%. By adjusting the process parameters of cellulose aerogel, the pore size of the prepared cellulose aerogel was 10-20 nm and the porosity was 96%.

[0123] 2) During the preparation of potassium silicate sol, the surfactant used in the SiO2 nanoparticle dispersion is lauryl alcohol phosphate, and the mass percentage of SiO2 in the SiO2 nanoparticle dispersion is 35%; during the preparation of the boron-containing potassium hydroxide solution, the surfactant is sorbitol, and the mass content of borax is 2.5%; the mass percentage of SiO2 in the potassium silicate sol is 30%.

[0124] 3) In the prepared heat-insulating protective glass, the SiO2 protective layer coated on the surface of the fire-facing glass is 90 nm, the thickness of the cellulose aerogel is 10 mm, and the thickness of the potassium silicate sol between the cellulose aerogel layer and the fire-facing glass is 5 mm.

[0125] The appearance of the formed heat-insulating fireproof composite glass was observed, and the light transmittance, haze, and heat-insulating fire-resistant effect of the glass were tested. The testing method was the same as in Example 1. The test results are shown in Table 1.

[0126] Example 4

[0127] The main difference between this embodiment and embodiment 1 is that the wood pulp raw material for preparing the cellulose aerogel is poplar wood pulp.

[0128] The appearance of the formed heat-insulating fireproof composite glass was observed, and the light transmittance, haze, and heat-insulating fire-resistant effect of the glass were tested. The testing method was the same as in Example 1. The test results are shown in Table 1.

[0129] Example 5

[0130] The main difference between this embodiment and Embodiment 1 is that the thickness of the SiO2 protective layer plated on a single side of the fire-facing glass layer of the prepared heat-insulating protective glass is 100 nm.

[0131] The appearance of the formed heat-insulating fireproof composite glass was observed, and the light transmittance, haze, and heat-insulating fire-resistant effect of the glass were tested. The testing method was the same as in Example 1. The test results are shown in Table 1.

[0132] Example 6

[0133] The main difference between this embodiment and embodiment 1 is that the thickness of the SiO2 protective layer plated on a single side of the fire-facing glass layer of the prepared heat-insulating protective glass is 50 nm.

[0134] The appearance of the formed heat-insulating fireproof composite glass was observed, and the light transmittance, haze, and heat-insulating fire-resistant effect of the glass were tested. The testing method was the same as in Example 1. The test results are shown in Table 1.

[0135] Example 7

[0136] The main difference between this embodiment and embodiment 1 is that only the ITO film is plated on a single side of the fire-facing glass layer of the prepared heat-insulating protective glass.

[0137] The appearance of the formed heat-insulating fireproof composite glass was observed, and the light transmittance, haze, and heat-insulating fire-resistant effect of the glass were tested. The testing method was the same as in Example 1. The test results are shown in Table 1.

[0138] Example 8

[0139] The main difference between this embodiment and embodiment 1 is that in the process of preparing the heat-insulating fire-resistant composite glass, the ITO transparent conductive film and the SiO2 protective layer are plated on the glass surface from the inside to the outside after the fire-facing glass is tempered.

[0140] The appearance of the formed heat-insulating fireproof composite glass was observed, and the light transmittance, haze, and heat-insulating fire-resistant effect of the glass were tested. The testing method was the same as in Example 1. The test results are shown in Table 1.

[0141] Example 9

[0142] The main difference between this embodiment and embodiment 1 is that the pore size of the prepared cellulose aerogel is 8-20 nm and the porosity is 90%. The cellulose aerogel prepared in this embodiment is used to prepare heat-insulating fireproof composite glass.

[0143] The appearance of the formed heat-insulating fireproof composite glass was observed, and the light transmittance, haze, and heat-insulating fire-resistant effect of the glass were tested. The testing method was the same as in Example 1. The test results are shown in Table 1.

[0144] Example 10

[0145] The main difference between this embodiment and embodiment 1 is that the thickness of the cellulose aerogel in the prepared heat-insulating fire-resistant composite glass is 3 mm.

[0146] The appearance of the formed heat-insulating fireproof composite glass was observed, and the light transmittance, haze, and heat-insulating fire-resistant effect of the glass were tested. The testing method was the same as in Example 1. The test results are shown in Table 1.

[0147] Embodiment 11

[0148] The main difference between this embodiment and embodiment 1 is that the thickness of the cellulose aerogel in the prepared heat-insulating fire-resistant composite glass is 15 mm.

[0149] The appearance of the formed heat-insulating fireproof composite glass was observed, and the light transmittance, haze, and heat-insulating fire-resistant effect of the glass were tested. The testing method was the same as in Example 1. The test results are shown in Table 1.

[0150] Example 12

[0151] The main differences between this embodiment and embodiment 1 are: the thickness of the potassium silicate gel layer between the fire-facing glass layer and the cellulose aerogel in the prepared composite glass is 20 nm; and the mass percentage of SiO2 in the prepared potassium silicate gel is 10%.

[0152] The appearance of the formed heat-insulating fireproof composite glass was observed, and the light transmittance, haze, and heat-insulating fire-resistant effect of the glass were tested. The testing method was the same as in Example 1. The test results are shown in Table 1.

[0153] Embodiment 13

[0154] The main difference between this embodiment and embodiment 1 is that in the prepared heat-insulating fire-resistant composite glass, cellulose aerogel prepared from coniferous larch wood pulp is used in the heat-insulating layer.

[0155] The appearance of the formed heat-insulating fireproof composite glass was observed, and the light transmittance, haze, and heat-insulating fire-resistant effect of the glass were tested. The testing method was the same as in Example 1. The test results are shown in Table 1.

[0156] Embodiment 14

[0157] The main difference between this embodiment and embodiment 1 is that in the process of preparing the composite glass, the thermal insulation layer only contains cellulose aerogel, and no potassium silicate gel layer is provided.

[0158] The appearance of the formed heat-insulating fireproof composite glass was observed, and the light transmittance, haze, and heat-insulating fire-resistant effect of the glass were tested. The testing method was the same as in Example 1. The test results are shown in Table 1.

[0159] Comparative Example 1

[0160] The difference between this comparative example and Example 1 is that in the process of preparing the composite glass, this comparative example only uses potassium silicate sol to bond the front-fire glass and the back-fire glass, and does not add a cellulose aerogel layer.

[0161] The appearance of the formed heat-insulating fireproof composite glass was observed, and the light transmittance, haze, and heat-insulating fire-resistant effect of the glass were tested. The testing method was the same as in Example 1. The test results are shown in Table 1.

[0162] Comparative Example 2

[0163] The difference between this comparative example and Example 1 is that the SiO2 nanoparticle dispersion used in the preparation of the potassium silicate sol contains a cationic surfactant polyacrylamide.

[0164] The appearance of the formed heat-insulating fireproof composite glass was observed, and the light transmittance, haze, and heat-insulating fire-resistant effect of the glass were tested. The testing method was the same as in Example 1. The test results are shown in Table 1.

[0165] Comparative Example 3

[0166] The difference between this comparative example and Example 1 is that the prepared composite glass is not provided with a butyl rubber layer.

[0167] The appearance of the formed heat-insulating fireproof composite glass was observed, and the light transmittance, haze, and heat-insulating fire-resistant effect of the glass were tested. The testing method was the same as in Example 1. The test results are shown in Table 1.

[0168] Table 1 Test results of various indicators of embodiments and comparative examples

[0169]

[0170]

[0171] In combination with Example 1, the accompanying drawings, and the data in Table 1, it can be seen that the heat-insulating fire-proof composite glass prepared by adopting the technical scheme of the present invention and within the parameter structure range required by the present invention has a long fire-resistant time and a low inner temperature. In actual use, the safety risk of the back area is significantly reduced, and the heating rate of the glass is slow, which further improves the safety of the back area.

[0172] Preferably, in combination with the implementation, it can be known that by using the insulating fire-proof composite glass and the preparation method thereof provided by the present invention, an ITO film is arranged from the inside to the outside on a single side of the fire-facing glass layer away from the insulation layer, and the SiO2 protective layer helps to increase the light transmittance of the glass; preferably, the thickness of the SiO2 protective layer is 60 to 90 nm.

[0173] Further preferably, in the process of preparing composite glass, the glass is coated before being tempered and strengthened. During the glass tempering process, the oxidation state and crystallization performance of the film layer are improved, thereby improving the photoelectric performance, and eliminating the separate heating step of the coating, thereby simplifying the process, improving production efficiency, saving energy, and thus saving costs.

[0174] Further preferably, controlling the porosity of the cellulose aerogel in the composite glass insulation layer to be uniform and the pore size to be within a certain range helps to improve the transmittance of the composite glass. This is because the cellulose aerogel has a too large porosity or an uneven pore size, and the composite glass prepared therefrom has an excessively large refractive index in the insulation layer of the composite glass under light irradiation, resulting in a decrease in the transmittance of the composite glass.

[0175] Further preferably, controlling the thickness of the cellulose aerogel layer in the composite glass insulation layer to be 6 to 10 mm helps ensure high light transmittance and optimal insulation effect of the composite glass.

[0176] Further preferably, the potassium silicate gel layer between the fire-facing glass layer and the cellulose aerogel in the composite glass is 1 to 5 mm, the mass percentage of SiO2 in the potassium silicate gel is 15 to 30%, and the prepared composite glass has high light transmittance, good refractive index matching, and good thermal insulation and fire resistance.

[0177] Further preferably, the optical and appearance properties of the composite glass obtained by using cellulose aerogel prepared from coniferous larch wood pulp are reduced. This is because the fibers prepared from pine wood pulp are relatively long, difficult to disperse, and relatively poor in uniformity.

[0178] By comparing the comparative example with the embodiment, it can be seen that if cellulose aerogel is not added to the composite glass, the thermal insulation effect of the prepared composite glass cannot meet the preset requirements; if the butyl rubber layer is not provided, water vapor in the environment will penetrate into the cellulose aerogel in the prepared composite glass, causing the gel to decompose and denature, resulting in defects such as bubbles and cracks.

[0179] When the method for preparing the heat-insulating fireproof composite glass disclosed in the present invention is used, if the SiO2 nanoparticle dispersion contains a cationic surfactant, bubbles and increased haze may appear in the composite glass, which is due to the uneven dispersion of the SiO2 nanoparticles.

[0180] The technical features in the claims and / or the specification of the present invention may be combined, and the combination is not limited to the combination obtained by reference in the claims. The technical solution obtained by combining the technical features in the claims and / or the specification is also within the protection scope of the present invention.

[0181] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. Any simple modification, equivalent change and modification made to the above embodiment according to the technical essence of the present invention still falls within the scope of the technical solution of the present invention.

Claims

1. A heat-insulating fire-resistant composite glass, characterized in that: It includes: The fire-facing glass layer comprises fire-facing glass; A heat-insulating layer is arranged on the surface of the fire-facing glass layer; the heat-insulating layer comprises a fiber aerogel core layer; A first potassium silicate gel layer and a second potassium silicate gel layer are provided on the upper and lower surfaces of the fiber aerogel core layer, and the fire-facing glass is connected to the heat insulation layer through the first potassium silicate gel layer; a butyl rubber layer is provided on the periphery of the four vertical side surfaces of the fiber aerogel core layer; The back-fire glass is arranged on the surface of the insulation layer, the back-fire glass layer includes the back-fire glass; the back-fire glass and the insulation layer are connected through a second potassium silicate gel layer; the surface of the butyl rubber layer is respectively connected to the front-fire glass layer and the back-fire glass layer.

2. The glass according to claim 1, characterized in that The front-fire glass and the back-fire glass are both borosilicate glass.

3. The glass according to claim 1, characterized in that The potassium silicate gel layer contains SiO2 with a mass percentage of 15-30%; the thickness of the first potassium silicate gel layer is 1-5 mm.

4. The glass according to claim 1, characterized in that The cellulose aerogel layer has a porosity of 95.0-99.5% and a pore size of ≤20 nm.

5. The glass according to claim 1, characterized in that The cellulose aerogel layer has a thickness of 6 to 10 mm.

6. The glass according to any one of claims 1 to 5, characterized in that: The single side of the fire-facing glass away from the heat insulation layer is coated with an ITO conductive film and a SiO2 protective layer from the inside to the outside.

7. A method for preparing heat-insulating fire-resistant composite glass, characterized in that: It includes the following steps: S71: cellulose aerogel is bonded to the middle position of the back-fired glass through potassium silicate gel; S72 A butyl rubber layer is adhered to the back-fired glass around the outer side of the cellulose aerogel; S73: bonding a fire-facing glass to the butyl rubber layer; the fire-facing glass, the butyl rubber layer, and the cellulose aerogel form a cavity; S74: Fill the cavity with potassium silicate gel.

8. The method according to claim 7, characterized in that The preparation of the cellulose aerogel comprises the following steps: Take a TEMPO aqueous solution with a mass concentration of 10-15% and a fiber suspension with a fiber mass percentage of 0.5-1%; Adding the TEMPO aqueous solution dropwise into the fiber suspension to form an oxidized fiber suspension, wherein the pH of the fiber suspension system is 9-10 during the addition process, and the volume percentage of the TEMPO aqueous solution in the oxidized fiber suspension is 20-30%; The oxidized fiber suspension is centrifuged to remove impurities to obtain a target fiber suspension; the fiber mass percentage in the target fiber suspension is 0.3-0.5%; The target fiber suspension is freeze-formed and freeze-dried in sequence to obtain cellulose aerogel.

9. The method according to claim 8, characterized in that The wood pulp fibers of the fiber suspension are derived from hardwood.

10. The method according to claim 7, characterized in that The preparation of the potassium silicate sol comprises the following steps: The SiO2 nanoparticle dispersion and the boron-containing potassium hydroxide solution are stirred and mixed at a temperature of 50 to 60° C. to form the potassium silicate sol; The SiO2 nanoparticle dispersion contains an anionic surfactant; The mass percentage of SiO2 in the potassium silicate sol is 15-30%.

11. The method according to claim 7, characterized in that Before the fire-facing glass is tempered, the side of the fire-facing glass away from the heat insulation layer is plated with an ITO transparent conductive film and a SiO2 protective layer from the inside to the outside.

12. The heat-insulating fireproof composite glass according to any one of claims 1 to 6, which can be used in the fields of construction, transportation, and industrial equipment.

Citation Information

Cited By

  • Automotive heat insulation glass with multi-layer composite structure and preparation method of automotive heat insulation glass

    CN121515559A